Pengaruh Supervisi Kepala Sekolah terhadap Mutu Pembelajaran dan Kinerja Guru - Muntahanah Muntahanah (Departement of Mathematics Education, 2023)
Conflicts in schools occur due to the appearance of incompetent teacher. The principal's performance can be optimal or not influenced by collaboration with other school personnel. The purpose of this study was to determine the supervisory system of school principals through academic supervision. The research method uses a qualitative library research approach using observation, interview, and documentation data collection techniques. The results of the study describe that supervision activities in schools are the responsibility of the principal as a teacher who has the additional task of supervising teacher performance and is responsible for improving educational progress including improving the learning system, improving the quality of teaching staff qualifications so that a structured and planned learning process is achieved with Good. Quality learning systems when supervision activities can run according to the instruments used based on data and facts in the school environment.